Vascular tissue engineering - Nerem, Robert (Henry Stewart Talks, 2007)
Tissue engineering approaches, Different cell sources for a blood vessel substitute, Circulating endothelial progenitor cells: their characteristics, their use in a blood cell substitute and recruitment from the host circulating blood, Differentiation from ES into endothelial cells in vitro and their endothelial-like characterization, The use of different types of scaffolds, In vivo and in vitro remodeling, Engineering immune acceptance, Clinical applications: EC-seeded ePTFE grafts for peripheral applications and cell-seeded polymer scaffold grafts for pulmonary artery/Fontan procedure